Tracking cryptic SARS-CoV-2 hospital outbreak through quasispecies analysis - Serena Messali; Marta Giovanetti; Alessandro Rondina; Marta Bertelli; Melissa Duheric; Francesca Caccuri; Massimo Ciccozzi; Arnaldo Caruso (Virology Journal, 2024)
Abstract Background Since the beginning of the pandemic, contact tracing has been one of the most relevant issues to understand SARS-CoV-2 transmission dynamics and, in this context, the analysis of quasispecies may turn out to be a useful tool for outbreak investigations. Analysis of the intra-host single nucleotide variants (iSNVs) found in the nsp2, ORF3, and ORF7 genes of SARS-CoV-2 was conducted in order to correctly identify virus transmission chain among patients hospitalized in Brescia Civic Hospital. Methods During the period between August and October 2023, 13 nasopharyngeal specimens, collected from patients admitted to Brescia Civic Hospital, were tested for SARS-CoV-2 positivity and molecularly characterized. Firstly, a phylogenetic analysis was performed to evaluate if they were epidemiologically linked and, then, the Beta-binomial method was used to estimate the transmission bottleneck size (Nb) and quantify the number of viral particles transmitted from one individual (donor) to another (recipient). Results According to the molecular characterization of specimens, we identified two transmission clusters in the cardiology unit: the first cluster concerned patients tested positive for the HV.1/EG.5.1.6 lineage, while the second cluster concerned patients tested positive for the FL.10.1 lineage. Moreover, evaluating the bottleneck size, we were able to solve SARS-CoV-2 transmission chain among infected patients. Conclusion Our method shows that it is possible to conduct a tracing study using a genomic approach based on iSNVs analysis.